If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8y + (-2y + 3) = 9 Reorder the terms: 8y + (3 + -2y) = 9 Remove parenthesis around (3 + -2y) 8y + 3 + -2y = 9 Reorder the terms: 3 + 8y + -2y = 9 Combine like terms: 8y + -2y = 6y 3 + 6y = 9 Solving 3 + 6y = 9 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 6y = 9 + -3 Combine like terms: 3 + -3 = 0 0 + 6y = 9 + -3 6y = 9 + -3 Combine like terms: 9 + -3 = 6 6y = 6 Divide each side by '6'. y = 1 Simplifying y = 1
| 6.5=1.5g+0.5 | | 4x+-7=3x | | 50=16t^2 | | 2(x+5)+x=46 | | 8y+5=9y | | 8y+(-2+3)=9 | | 11(4-6y)+5+(13y+1)=9 | | 4x+5=4x-10 | | 4a^2+20a+25=0 | | 7x-3+2x=9x-8x | | 5(x-4)=2x+1 | | 5x+7-6x=-32 | | 5-9x=2-8x | | 5x+4=x | | 5-5(5w-4)+w= | | 1f=6 | | (x-3)(x+3)=8x | | 5x-15=3x-5 | | 17y=10y+21 | | -0.25+3+2= | | 6x-2-4x=2 | | -9(-1+3b)= | | 18-(9+3)+2= | | -68+6x=-4x+112 | | -3x+(x-1)=-12 | | 18X-3-5x=33-5x | | 6(3a+1)-30=(2a-4) | | 18x=12x+3 | | 7-8x=5-7x | | 2(6+-6h)= | | 24=5t^2 | | 2+3(4y-2)=20 |